Data Usability: The Forgotten Segment of Environmental Data Workflows - Dosemagen, Shannon; Williams, Emelia (Frontiers in Climate, 2022)
While there has been a rapid increase in the use of participatory science methods over the last decade, the usability of resulting data in addressing situations of environmental injustice is often overlooked, neglected, or used as political fuel for ignoring inconvenient truths. The inability of data to be used for policy, regulation, and enforcement impedes its usefulness in various situations depending on user requirements and governance scales. On the other hand, there are vast open datasets that could be useful for communities and researchers, but these data are often difficult to find, use, or repurpose, beyond their original intent. This article unpacks the data usability problem at the frontier of environmental governance and decision-making, suggesting that by prioritizing environmental data as a public good, there are clear mechanisms for ensuring data usability towards participatory environmental governance. The authors are interested in uncovering the policies and behavioral and bureaucratic patterns that have remained static as participatory science methods and tools have advanced. It is necessary to understand where and when associated tools, methods, and platforms have failed to ensure that data is usable and useful for communities attempting deeper engagement and representation in environmental governance.